Is psoriasis an independent risk factor of renal disease? A nationwide retrospective cohort study from 1996 to 2010 - Sebastian Yu; Hung-Pin Tu; Chu-Ling Yu; Chih-Hung Lee; Chien-Hui Hong (Wolters Kluwer Medknow Publications, 2017)
Background: Psoriasis is a chronic inflammatory disease that affects the skin, joints, and cardiovascular system. Although a potential association of end-stage renal disease (ESRD) with psoriasis has been demonstrated in patients, the potential for the use of cyclosporin in these patients for the modulation of the course of ESRD remains doubted. Furthermore, the association between psoriasis and renal diseases in general remains unclear. This study aimed to investigate the risk of renal disease in psoriatic patients with or without the use of cyclosporin. Methods: We performed a retrospective cohort study using the National Health Insurance Database of Taiwan from 1996 to 2010 to identify patients with psoriasis, renal disease, chronic renal failure, and ESRD, and the use of cyclosporin. Overall, 3502 psoriatic patients and 10,506 matched population comparisons were identified. The hazard ratios (HRs) for renal events during the follow-up period were computed. Results: Patients with psoriasis had an increased risk of chronic renal failure [HR = 3.00; 95% confidence interval (CI), 2.30-3.93; p < 0.0001] and ESRD (HR = 2.03; 95% CI, 1.04-3.96; p = 0.0393). Cyclosporin increased the risk of renal disease in patients without psoriasis (HR = 6.34; 95% CI, 3.57-11.26; p < 0.0001), but not in patients with psoriasis (HR = 1.33; 95% CI = 0.66-2.69; p = 0.4299). Conclusion: Psoriasis is an independent risk factor of chronic renal failure and ESRD. Cyclosporin, a commonly used antipsoriatic agent, does not significantly increase the risk of renal disease in patients with psoriasis. Further studies with larger sample size are indicated to validate this result.